2018
DOI: 10.1016/j.fm.2018.05.011
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the efficacy of multiple physical, biological and natural antimicrobial interventions for control of pathogenic Escherichia coli on beef

Abstract: Antimicrobial effects of multiple physical, biological and natural interventions on pathogenic Escherichia coli in raw beef were assessed. A cocktail of E. coli strains was inoculated onto gamma-irradiated beef and enumerated immediately after each intervention and during storage at 4 °C for 7 days. Of the physical interventions, silver-containing antimicrobial packaging and ozone gas treatment did not show significant antimicrobial effects, however cold plasma treatment reduced E. coli levels by 0.9 and 1.82 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
26
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(30 citation statements)
references
References 65 publications
3
26
0
1
Order By: Relevance
“…Although the used concentrations of lactic and acetic acids showed a great antibacterial effect, they have no adverse effect on the sensory and organoleptic examinations of the carcass's meat. This character was previously reported by (Stratakos and Grant, 2018) where they reported that, the diluted solutions of organic acids (1 to 3%) are generally don't affect the wholesome organoleptic properties of fresh meat when used as a carcass decontaminant. In addition, this study recorded that lactic acid showed greater inhibitory effect than acetic acid in the same concentrations.…”
Section: Discussionsupporting
confidence: 67%
“…Although the used concentrations of lactic and acetic acids showed a great antibacterial effect, they have no adverse effect on the sensory and organoleptic examinations of the carcass's meat. This character was previously reported by (Stratakos and Grant, 2018) where they reported that, the diluted solutions of organic acids (1 to 3%) are generally don't affect the wholesome organoleptic properties of fresh meat when used as a carcass decontaminant. In addition, this study recorded that lactic acid showed greater inhibitory effect than acetic acid in the same concentrations.…”
Section: Discussionsupporting
confidence: 67%
“…Combinations of natural antimicrobials, similar to AuraShield L (e.g. Auranta 3001), were previously described as efficient in preventing bacterial infections in chicken and mouse animal models [13][14][15][16] . These results show that Auranta 3001 has a negative impact on the expression of virulence genes in Campylobacter spp.…”
mentioning
confidence: 99%
“…The anti-virulent effect of natural antimicrobial mixtures was previously described in other pathogens e.g., Campylobacter jejuni, Campylobacter coli and Shiga Toxin Producing E. Coli (STEC) [13,41]. This anti-virulent effect was exhibited by decreasing the activity of major virulence factors including motility, and by reducing the in vitro and in vivo infection abilities, T6SS and biofilm formation [13,42].…”
Section: Discussionmentioning
confidence: 84%